Ekho rossiiskogo vybora. . Ekho rossiiskogo vybora. . Echo of Russian Choice . Эхо российского выбора - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Interview with the economist Otto Latsis about the Moscow revolt on October 3-4, 1993; Western reaction to these events; interview with Anatoly Saran, Ambassador of Moldova in Russia; polling ordinary Ukrainians about their political preferences. Featured in the program: Latsis, Otto Rudol'fovich (Economist); Pauls, Raimonds (Composer) Contributors: Tarasova, Alla (Director); Samarin, Viktor (Anchor) Интервью с экономистом Отто Лацисом о мятеже в Москве 3-4 октября 1993 года; западная реакция на эти события; интервью с Анатолием Сараном, послом Молдовы в России; опрос обычных украинцев об их политических предпочтениях. В программе участвуют: Лацис, Отто Рудольфович (Экономист); Паулс, Раймонд (Композитор) Создатели: Тарасова, Алла (Режиссер); Самарин, Виктор (Ведущий/Ведущая)